Involvement of T cells in early evolving segmental vitiligo. (1st August 2016) - Shin, J.; Kang, H. Y.; Kim, K. H.; Park, C. J.; Oh, S. H.; Lee, S. C.; Lee, S.; Choi, G. S.; Hann, S. K.
Summary: Recent studies have suggested an overlapping autoimmune mechanism between segmental vitiligo (SV) and nonsegmental vitiligo (NSV). Although T‐cell infiltration is observed in the margins of active lesions in NSV, the histopathological characteristics of the active margin of SV are not well known. To determine if T‐cell inflammatory responses are present in the active margin of SV lesions, biopsies were taken from the active margin of a lesion in 12 patients with early or actively spreading SV and compared with a normal control sample (on the symmetrical, opposite site of the same dermatome). The samples were stained for CD4, CD8, CD25 and interferon‐γ. Lymphocytic infiltration was seen in 70% of patients. CD4+ T cells infiltrated the dermis, while CD8+ T cells were present in the epidermis or attached to the basal layer. The increase in the number of CD8+ T cells was significant ( P < 0.04), while CD4+ or CD25+ T cells also appeared to be increased in number, but this was not significant. These results suggest that SV also has an autoimmune mechanism in the early evolving stage.